Lymphogranuloma venereum presenting as perianal ulceration: an emerging clinical presentation?. Issue 2 (26th January 2011) - Singhrao, Tajinder; Higham, Elizabeth; French, Patrick
Abstract : An outbreak of lymphogranuloma venereum (LGV) infection has been recognised in the UK since 2004, predominantly affecting HIV-positive men who have sex with men (MSM). Patients typically present with proctitis symptoms. The prevalence of rectal LGV in MSM attending sexually transmitted infection clinics in London is estimated at 1%. Health Protection Agency surveillance has shown a decrease in anorectal manifestations despite little demographic change. Two cases of HIV-infected patients presenting with isolated perianal ulcer disease are reported here. Both cases were confirmed to have rectal Chlamydia trachomatis -specific DNA of an LGV associated serovar. As presentations of LGV diversify, further education and surveillance are needed in order to reduce transmission and prevent long-term complications. A strong argument already exists for the incorporation of chlamydia nucleic acid amplification tests in the management of MSM with proctitis; this paper provides evidence that this should be extended to MSM with perianal ulcer disease.